Chemical composition of Lycium europaeum fruit oil obtained by supercritical CO2 extraction and evaluation of its antioxidant activity, cytotoxicity and cell absorption. (1st September 2017) - Rosa, Antonella; Maxia, Andrea; Putzu, Danilo; Atzeri, Angela; Era, Benedetta; Fais, Antonella; Sanna, Cinzia; Piras, Alessandra
Highlights: Oil was obtained from Lycium europaeum fruits by supercritical CO2 extraction. The oil showed high levels of carotenoids, phenols, and essential fatty acids. Fixed oil exhibited radical scavenging activity against DPPH and ABTS + radicals. L. europaeum oil exerted a significant cytotoxic effect on Caco-2 cells. Differentiated Caco-2 cells treated with oil accumulated essential fatty acids. Abstract: We studied the total phenols and flavonoids, liposoluble antioxidants, fatty acid and triacylglycerol profiles, and oxidative status of oil obtained from Lycium europaeum fruits following supercritical CO2 extraction (at 30 MPa and 40 °C). Linoleic (52%), palmitic (18%), oleic (13%), and α-linolenic (6%) were the main oil fatty acids, while trilinolein and palmitodilinolein/oleodilinolein represented the main triacylglycerols. The oil was characterized by high levels of all- trans -zeaxanthin and all- trans -β-carotene (755 and 332 μg/g of oil, respectively), α-tocopherol (308 μg/g of oil), total phenols (13.6 mg gallic acid equivalents/g of oil), and total flavonoids (6.8 mg quercetin equivalents/g of oil). The oil showed radical scavenging activities (ABTS and DPPH assays) and inhibited Caco-2 cell growth. Moreover, the incubation of differentiated Caco-2 cells with a non-toxic oil concentration (100 μg/mL) induced a significant intracellular accumulation of essential fatty acids. The results qualify L. europaeum oil as a potential source for food/pharmaceutical applications.